Mejorar y socializar el código de convivencia para que se cumpla este principio de la educaciòn y así desarrollar las relaciones sociales entre los miembros de la comunidad educativa “Nuestra Señora de Pompeya” del cantón Saquisilí en el año 2012-2013 - Correa Venegas, Miriam Natali (2015)
Is this research use the logical-inductive method because after doing the research on how social relationship involved of Nuestra Señora de Pompeya high school it determined there is a rulebook that students, authorities and parents didn’t apply such as: the discipline that often are taught from their homes, by excess children receive consent by family members and institutional problems almost daily lives in this institution. That’s why as researchers it will modify this rulebook with new changes that allow a more demanding and creative teaching values to children, parents, teachers and neighbors, it’s important to have values such as: respect, honesty, sincerity and love for everybody to implement recreational workshops, conferences to train members of the institution whit main values in the education of children and ensure that students are educated in an educational environment and respectful.